(3eYjGQ CZhGQ GdCagGe aj GdcTa Yf efGSHGJ GdCMcGes - (3YHO Gddg Hf eMeO Hf CHj GdbGSe GdRjOj GdYHSj GdfLQj, GdfLQj,J (B877 (3g` s ((3Ydi Hf MSf Hf CMeO GdYjOQi GdYfGHi s)
(3ChdgG (B:s
(3jGef cd CMcGeg HYR GdMceI eYbhOI , hLejY CaYGdg HGdCZQGV GdMUMjI ehLhOI , cdJ GdCdSfI Yf GdhaGA dc HGdTcd s
(3BNQgG (B:s
(3aEf CJdag ef gh ai jOg HYO GdWdH de jVefg EdG HGdCKe , cSGFQ GdMbhb Je gPG GdcJGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3HChdgG agQSJ ddehVhYGJs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs